Финансы предприятий: учебник для студентов вузов, обучающихся по экон. спец. / Л.Н. Павлова - Павлова Лариса Николаевна (Финансы, 1998)
Экземпляры: аб. (1999) / Инвентарный номер: 40940 / Цена: / Сис.шифр: 65.290 / Авт.знак: П 12 / ГРНТИ: 06.81 / ББК: 65.290-93я73